What do we know about the future of agri-food systems in Southeast Asia? - Tran, Nhuong; Valera, Harold Glenn; Chan, Chin Yee; Pede, Valerien; Aung, Yee Mon (CGIAR, 2023)
Key messages The food systems of Southeast Asia (SEA) are projected to be under increasing pressure due to multiple drivers including population growth, urbanization, biodiversity loss, and the uncertainties stemming from climate change. Rice and fish will remain staple foods and the backbone of diets in the region, in both rural and urban areas. In 2019, SEA was responsible for 72% of world’s aquatic food products and 90% of global rice production. Rice provides 50% of calorie intake for its population, while fish consumption contributes more than 50% per capita average animal protein intake. These shares are expected to rise over the next several decades due to population growth. Production and consumption of staple foods is expected to fall due to the impacts of climate change, potentially jeopardizing the food and nutrition security in the region and other regions of the world. The magnitude of climate change impacts on rice production has large uncertainty depending on the models used. Previous regional foresight studies have explored the implications of climate change on food production in SEA, but other driving forces and outcomes of food system transformation have received less attention.